Digital Student Master Book to Support the Principal’s Managerial Role in Elementary Schools of Rembang Regency - Kukuh Adi Prasetio; Rasiman; Qristin Violinda (Journal of Education Reseach and Evaluation, 2025)
The management of the student master book in elementary schools is still carried out manually, which creates variuos obstacles, including the risk of document damage, data loss, and delays in retrieving information. This research aims to develop a digital student master book that is valid, practical, and effective to suport the role of principals as managers. The research method employed is Research and Development (R&D) with eight stages, namely potential and problems, data collection, product design, product validation, product revision, product testing, product revision, and implementation testing. The validation results from material experts and media experts showed a percentage score of 98.7%, classified as very valid. The practicality test conducted by principals and teachers showed an average percentage score of 98.1%. The effectiveness test indicated an N-Gain score of 0.876, and the paired t-test results confirmed a statistically significant difference. Therefore, the digital student master book is declared valid, practical, and effective in supporting the role of principals as managers. The implication is that the development of the Digital Student Master Book can strengthen the managerial role of school principals in data management and decision-making based on accurate and efficient information. Furthermore, the implementation of this digital innovation has the potential to increase transparency, accountability, and effectiveness of elementary school management.